Tray Dryer's Performance in the Drying of Banana Slices Using LPG and Wood Stove - Devi Yuni Susanti; Joko Nugroho Wahyu Karyadi; Octavia Arini; Septi Agustiani Fajriyah; Sri Rahayoe; Hanim Zuhrotul Amanah (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2024)
An evaluation was carried out on a simple tray dryer of banana slices in the